Motivation solutions for small and medium-sized enterprises in the Southern Transdanubian Region - Boldizsár, Bettina; Bardóczky, Veronika; Szigeti, Orsolya (Applied Studies in Agribusiness and Commerce, 2020)
The singularity of human resources and the complex interests in the world of work are a constant challenge for business executives and HR colleagues. While the difference between the performance of a motivated and an unmotivated employee can be up to twice as much at almost the same cost level, the motivation strategy is typically either absent from the business life, or operates on a reactive concept based on an unconscious design. Although the mere presence of motivation and its various levels are less quantifiable in exact terms with direct tools, a performance which is much weaker than possible is measurable in the short and long term, and its negative economic results are clear. The aim of the research is to examine the motivational practices of small and medium-sized enterprises (SMEs) operating in the Southern Transdanubian Region. Involving 300 businesses we evaluated the applied wage system, the role of money among the motivational tools, the extent and causes of fluctuation, the system of employee training, the way of performance evaluation, the reasons for underperformance, the importance of motivation, the company motivation strategy and the efforts to retain the key people. The employee motivation can be increase in several forms, but the priority of needs and claims is constantly changing. Updating this motivational matrix is a real leadership challenge, but this effort can pay off multiple times. According to the results it can be stated that the motivation strategy – as a key economic issue – is not given sufficient attention in business practices.